Spectroscopic investigation of the ultrasound impacts on the molecular structures of blood proteins - Aysh Y. Madkhli; Waad A. Al-Otaibi; Sahar M. AlMotwaa; Amal Mohsen Alghamdi; Norah T.S. Albogamy; Manal A. Babaker; Eida M. Alshammari; Mohammed J. Al Nahari; Abdu Saeed (Chemical Physics Impact)
Low-frequency ultrasound waves (LFUWs) are applied in various medical treatments, but their effects on blood proteins’ molecular structure are not well understood. This study explores how LFUWs alter blood protein structures, utilizing ultraviolet-visible (UV–vis), Raman, and Fourier transform infrared (FTIR) spectroscopies. Blood samples from five volunteers were subjected to LFUWs for periods of 0, 5, 10, 15, and 20 min. Multivariate analyses, including hierarchical cluster analysis (HCA) and principal components analysis (PCA), were performed to distinguish between the spectroscopic data of control samples and those exposed to LFUWs. Results from UV–vis spectroscopy indicated hemolysis and changes in hemoglobin (Hb) and amino acids after more than 10 min of LFUW exposure. Raman spectroscopy showed a negative correlation between LFUW exposure time and intensity ratio, hinting at Hb deoxygenation and structural changes. FTIR spectroscopy revealed an increase in α-helices and a decrease in random coils, β-sheets, and turns in samples exposed to 10 min or more of sonication. These findings suggest that LFUW exposure could cause blood protein denaturation, likely through localized hyperthermia induced by ultrasound waves. This study highlights the potential of LFUWs to induce protein denaturation and demonstrates the effectiveness of UV–vis, Raman, and FTIR spectroscopy in investigating the impacts of ultrasound on biomolecular structures.